Problem Yuridis Penyelesaian Perkara HAM Berat dalam Sistem Pidana Indonesia dan Pidana Islam - Mohammad Ali; Moh. Abd. Rauf (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2021)
The expound of human rights cases in Indonesia can not become a problem solver since the enactment of the Human Rights Law in 1999 and the law on the Human Rights Court in 2000. Juridical constraints are the most striking factor in the weak resolution of severe human rights cases, especially in proving and resolving severe human rights cases in the criminal procedural law system. The result of the discussion is that the procedural law for the settlement of human rights cases (Law No. 26 of 2000) still does not accommodate the needs of law enforcement, especially in the investigation process. National Commission on Human Rights (Komnas HAM)'s authority tends to be politically intervened. So that, in the future, it is necessary to adjust the law enforcement system with the rules that have been applied. Whereas as a country with an Islamic majority, although it does not base its laws on Islamic Law; at least the values ​​of Islamic criminal law can be realized from every law enforcement carried out, especially in upholding human rights, which in Islamic Law become the leading benchmark in seeing and enforcing a law. Abstrak: Penanganan kasus HAM di Indonesia masih dapat dikatakan belum mampu menjadi problem solver sejak diundangkan UU HAM pada tahun 1999 dan UU Pengadilan HAM pada tahun 2000. Kendala yuridis menjadi faktor paling mencolok terhadap lemahnya penyelesaian kasus HAM berat. Terutama pada konteks pembuktian dan penyelesaian perkara HAM berat dalam sistem hukum acara pidana. Hasil dari pembahasan bahwa dalam hukum acara penyelesaian kasus HAM (UU No 26 Tahun 2000) masih belum mengakomodir kebutuhan penegak hukum terutama dalam proses penyidikan. Kewenangan Komnas HAM yang condong selalu diintervensi secara politis. Sehingga ke depan perlu penyesuaian dalam sistem penegakan hukum dengan aturan yang sudah diterapkan. Padahal sebagai negara dengan mayoritas Islam, meski tidak mendasarkan hukum terhadap hukum islam; paling tidak nilai-nilai dari hukum pidana islam dapat diwujudkan dari setiap penegakan hukum yang dilakukan, terutama dalam menegakkan hak-hak asasi manusia yang dalam hukum islam menjadi tolok ukur utama dalam melihat dan menegakkan suatu hukum.